Establishing the regional center on biodiversity data mobilization in the Northwestern Siberia (Russia) - Filippova, Nina V.; Filippov, Ilya V.; Lapshina, Elena D. (ARPHA Proceedings, III Russian National Conference “Information Technology in Biodiversity Research”, 2020)
The initiatives on data mobilization in biodiversity science have been steadily on the rise throughout the past few decades. The Global Biodiversity Information Facility (GBIF) supports this development and enables open access to biodiversity data on an international scale. In Russia, with its immense territory, the initiative is following a unique course; while some regions are well-represented, others are hardly ever mentioned. The operational unit in the GBIF network is a GBIF Participant Node, which coordinates a country or organization to collectively develop an infrastructure for delivering biodiversity information. The Nodes, however, are formally established in countries which become Voting or Associate participants in GBIF, which is not yet the case for Russia. The large size of our country would justify the need to create sub-nodes of the next level. This publication is describing process of establishing a regional initiative in the northern part of West Siberia – within the administrative boundaries of the Khanty-Mansi Autonomous Okrug-Yugra, Yamal-Nenets Autonomous Okrug and Tyumen region. The regional initiative started in 2018, although some biodiversity information initiatives had been developing earlier (since 2012). The work currently covers four main areas of GBIF-nodes responsibilities and services: coordination the landscape of initiatives, support of biodiversity data mobilization, biodiversity data analysis and use, and support of data management and curation. These services are described in more detail in the present paper, and problems in the development of individual services are discussed. By the end of 2020, there are 11 registered publishing organizations and 37 published datasets from the Siberian Northwest. The total number of published records is about 120 000, with 30% published by the Yugra State University; 20% are observations from iNaturalist.org; all organizations in Northwestern Siberia as a whole represent about 50% of the published records.